Fifty Shades of the Harlequin Ladybird and a Sexually Transmitted Fungus - Fiedler, Lukáš; Nedvěd, Oldřich (Oxford University Press, 2019)
The ectoparasitic fungus Hesperomyces virescens was studied on its invasive host, the harlequin ladybird Harmonia axyridis, in the Czech Republic. A primary aim was to examine the relationship between fungal infection and elytral coloration of the ladybird. Furthermore, the role of host sex and mating status of females were analyzed. Beetles (n = 1,102) were sampled during autumn migration, and then sexed, weighed, and screened for infection. Females were dissected for detection of sperm in their spermathecae. Ladybirds were sorted according to color form and absorbance spectrophotometry was used to quantify carotenoid contents in their elytra. In individuals of the nonmelanic succinea form, the degree of melanization was measured using digital photographs and putative age groups were estimated based on background color of elytra. Sexual differences in infection patterns indicated transmission during copulation: males were infected mostly on elytra and venter, and females had infection almost exclusively on elytra. Mated females had higher infection rate than virgins.There was no influence of genetic color form on the fungal infection. Putative age groups (visual sorting to yellow, orange, and red) correlated with fungal infection. Infected individuals had elevated elytral carotenoid levels in comparison to uninfected individuals, which could be explained by host age. Infection-free succinea beetles were extensively melanized because they emerged later in the season at lower temperatures which induced melanization. Overall, we highlight that H. axyridis is a multivoltine species whose age, if not taken into account in ecophysiological studies, might present a considerable confounding factor.
Keywords: Harmonia axyridis; Hesperomyces virescens; color pattern; carotenoids; melanism